Hubungan antara Komposisi Kimia Aspal dan Sifat Rheologi Aspal - Tjitjik Wasiah Suroso (Jurnal Jalan-Jembatan, 2005)
The article presents the research result on the relationship between chemical properties and rheological properties of several asphalt samples as road pavement materials. The research was conducted in the following ways 1) chemical analysis to determine the content of asphalten and the parameters of malten composition as the comparison between the number of nitrogen fraction base plus acidafit I and Acidafit II plus paraffin before and after heating. 2) to determine rheological properties of asphalt, asphalt penetration, weight decrease (evaporation of light fraction) before and after heating, asphalt penetration ratio (ageing). Determination of asphalt malten composition parameters was done by solubility and precipitation method developed by Stenberg Rostler. The result showed that there is a relationship between malten composition parametr, asphalten content, penetration before and after heating. Asphalten content is indentical to asphalt penetration value (asphalt hardness), high content of asphalten, low asphalt penetration. Asphalt Weight decrease (fraction evaporation) does not parallel with the parameter of malten conposition value eventhough light fraction changed into densed fraction due to heating. In general, there is no significant relationship between the change of asphalt chemical properties as a result of heating and asphalt ageing. In Other words, the change of chemical properties indefinitely parallel with the change of rheological asphalt properties. Therefore, asphalt durability cannot be determined from malten composition value or asphalt chemical composition and cannot be used as a reference in the evaluation of road pavement failure. Further research is required to find out the relationship between asphalt chemical properties and mechanical properties of asphalt mixes so that the findings can be used to predict the durability of road pavements.